Partially hydrolyzed guar gum increased colonic mucus layer in mice via succinate-mediated MUC2 production - Mariko Kajiwara-Kubota; Kazuhiko Uchiyama; Kohei Asaeda; Reo Kobayashi; Hikaru Hashimoto; Takeshi Yasuda; Satoshi Sugino; Takeshi Sugaya; Yasuko Hirai; Katsura Mizushima; Toshifumi Doi; Ken Inoue; et al. (npj Science of Food, 2023)
Abstract Colonic mucus layers protect intestinal tissues against intestinal bacteria. We investigated the effects of dietary fiber and its metabolites on mucus production in the colonic mucosa. Mice were fed a partially hydrolyzed guar gum (PHGG)-containing diet and a fiber-free diet (FFD). The colon mucus layer, fecal short-chain fatty acid (SCFA) levels, and gut microbiota were evaluated. Mucin 2 (MUC2) expression was assessed in SCFA-treated LS174T cells. The role of AKT in MUC2 production was investigated. The mucus layer in the colonic epithelium was significantly increased in the PHGG group compared with that in the FFD group. In the PHGG group, an increase in Bacteroidetes in the stool was observed, and fecal acetate, butyrate, propionate, and succinate levels were significantly increased. However, MUC2 production was significantly increased only in succinate-stimulated LS174T cells. The succinate-induced MUC2 production was associated with AKT phosphorylation. Succinate mediated the PHGG-induced increase in the colon mucus layer.